Ventilation of subterranean CO2 and Eddy covariance incongruities over carbonate ecosystems - F. Domingo; C. Moreno de Jong; L. Villagarcía; P. Serrano-Ortiz; A. Were; A. S. Kowalski (Biogeosciences, 2010)
Measurements of CO2 fluxes with Eddy Covariance (EC) systems are ongoing over different ecosystems around the world, through different measuring networks, in order to assess the carbon balance of these ecosystems. In carbonate ecosystems, characterized by the presence of subterranean pores and cavities, ventilation of the CO2 accumulated in these cavities and pores can act as an extra source of CO2 exchange between the ecosystem and the atmosphere. In this work we analyse the effect of the subterranean heterogeneity of a carbonate ecosystem on measurements of CO2 fluxes by comparing measurements from two EC systems with distinct footprints. Results showed that both EC systems agreed for measurements of evapotranspiration and of CO2 in periods when respiratory and photosynthetic processes were dominant (biological periods), with a regression slope of 0.99 and 0.97, respectively. However, in periods when the main source of CO2 comes from the ventilation of subterranean pores and cavities (abiotic periods) agreement is not good, with a regression slope of 0.6. Ground-penetrating radar measurements of the sub-surface confirmed the existence of high sub-surface heterogeneity that, combined with different footprints, lead to differences in the measurements of the two EC systems. These results show that measurements of CO2 fluxes with Eddy covariance systems over carbonate ecosystems must be taken carefully, as they may not be representative of the ecosystem under consideration.